Characterizations of the viability and gene expression of dispersal cells from Pseudomonas aeruginosa biofilms released by alginate lyase and tobramycin. - Said M Daboor; Renee Raudonis; Zhenyu Cheng (PLoS ONE, 2021)
Biofilm infections are hard to manage using conventional antibiotic treatment regimens because biofilm structures discourage antibiotics from reaching the entire bacterial community and allow pathogen cells to persistently colonize and develop a plethora of tolerance mechanisms towards antibiotics. Moreover, the dispersed cells from biofilms can cause further complications by colonizing different sites and establishing new cycles of biofilms. Previously, we showed that alginate lyase enzyme (AlyP1400), purified from a marine Pseudoalteromonas bacterium, reduced Pseudomonas aeruginosa biofilm biomass and boosted bactericidal activity of tobramycin by degrading alginate within the biofilm extracellular polymeric substances matrix. In this work, we used a flow cytometry-based assay to analyze collected dispersal cells and demonstrated the synergy between tobramycin with AlyP1400 in enhancing the release of both live and dead biofilm cells from a mucoid P. aeruginosa strain CF27, which is a clinical isolate from cystic fibrosis (CF) patients. Interestingly, this enhanced dispersal was only observed when AlyP1400 was combined with tobramycin and administered simultaneously but not when AlyP1400 was added in advance of tobramycin in a sequential manner. Moreover, neither the combined nor sequential treatment altered the dispersal of the biofilms from a non-mucoid P. aeruginosa laboratory strain PAK. We then carried out the gene expression and tobramycin survival analyses to further characterize the impacts of the combined treatment on the CF27 dispersal cells. Gene expression analysis indicated that CF27 dispersal cells had increased expression in virulence- and antibiotic resistance-related genes, including algR, bdlA, lasB, mexF, mexY, and ndvB. In the CF27 dispersal cell population, the combinational treatment of AlyP1400 with tobramycin further induced bdlA, mexF, mexY, and ndvB genes more than non-treated and tobramycin-treated dispersal cells, suggesting an exacerbated bacterial stress response to the combinational treatment. Simultaneous to the gene expression analysis, the survival ability of the same batch of biofilm dispersal cells to a subsequent tobramycin challenge displayed a significantly higher tobramycin tolerant fraction of cells (~60%) upon the combinational treatment of AlyP1400 and tobramycin than non-treated and tobramycin-treated dispersal cells, as well as the planktonic cells (all below 10%). These results generate new knowledge about the gene expression and antibiotic resistance profiles of dispersed cells from biofilm. This information can guide the design of safer and more efficient therapeutic strategies for the combinational use of alginate lyase and tobramycin to treat P. aeruginosa biofilm-related infections in CF lungs.